INTEGRATION OF LOCAL WISDOM INTO PROBLEM-BASED BOOKS WITH AUGMENTED REALITY TO IMPROVE STUDENTS' CONSERVATION LITERACY - Iwan Iwan; Jeni Jeni; Nurfathurrahmah Nurfathurrahmah; Sumaifa Sumaifa (JURNAL EDUSCIENCE, 2026)
Purpose – Students' conservation literacy could be greatly increased by integrating local knowledge with the PBL approach and augmented reality technology. In order to increase students' conservation literacy, this study aimed to create a student book on biodiversity that was focused on problem-based learning, incorporated local knowledge, and supported by augmented reality media.Methodology – The ADDIE paradigm of research and development is referred to as the research technique. Manokwari high school students served as the study's 32 subjects. Validation sheets and questionnaires were used as data collection tools to assess the validity of the student book and the students' answers to conservation literacy questions. Students' replies, validation results, and conservation literacy abilities were all examined in the descriptive data analysis.Findings – The findings of this study indicate that the validation results for the Biodiversity Student Book were 93.65% (very valid category), indicating that it is suitable for implementation in learning. The validation of the conservation literacy instrument yielded a 96.13% validity rate (very valid). The results of student responses after the trial of the student book in learning were 85% (very practical or effortless to use category). The results of the trial evaluating the effectiveness of student conservation literacy showed a Sig of 0.000 (<0.05), indicating a difference in the average level of student conservation literacy before and after learning.Contribution – This study concludes that the use of student books on biodiversity is highly effective in improving and developing students' conservation literacy